Quantitative determination of the content of venlafaxine and its active metabolite in human plasma using liquid chromatography-mass spectrometry - I. I. Kuzmin; A. I. Platova; A. S. Konstantinova; I. I. Miroshnichenko (LLC "Publisher OKI", 2023)
A validated method for the quantitative determination of venlafaxine, O-desmethylvenlafaxine in human plasma by tandem liquid chromatographymass spectrometry (HPLC/MS/MS) has been proposed. Sample preparation was carried out by liquid-phase extraction with support (SLE, from «supported liquid extraction») using HyperSEP cartridges and washing with 3-methylbutyl ether. The measure of the target analytes was carried on a triple quadrupole mass spectrometer under multiple-reaction monitoring (+MRM) mode with the electrospray ionization. The calibration curves were linear with regression coefficient r2 > 0.999. The method validation was showed high sensitivity, specificity, accuracy and reproducibility, as well as stability of analytes after freeze/thaw cycles and storage at -20 °C. The method is developed for using in therapeutic drug monitoring.